2020
DOI: 10.1590/2317-1782/20202018295
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de audição e linguagem pós implante coclear em crianças com síndrome de Waardenburg

Abstract: RESUMO A Síndrome de Waardenburg (SW) é uma condição genética rara de padrão autossômico dominante e que pode cursar com perda auditiva neurossensorial. Nesse relato, apresentamos o desempenho da audição e linguagem de três crianças com SW, com zero, três, nove, doze e sessenta meses de seguimento após implante coclear (IC). As crianças foram avaliadas através dos questionários Escala de Integração Auditiva IT-MAIS (até 5 anos), MAIS (maiores de 5 anos), Escala de Utilização da Fala (MUSS) e categorizados quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 12 publications
0
12
0
2
Order By: Relevance
“…Five studies reported on intra‐ or post‐operative complications 15,24,28,31,38 . A total of 12 complications were reported in as many patients.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies reported on intra‐ or post‐operative complications 15,24,28,31,38 . A total of 12 complications were reported in as many patients.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were published between 2000 and 2022. Study characteristics are summarized in Table 1 15,24–38 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations